2012
DOI: 10.1111/j.1365-2389.2011.01420.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of specific peaks obtained by diffuse reflectance Fourier transform mid‐infrared spectroscopy to study the composition of organic matter in a Haplic Chernozem

Abstract: This study assessed specific peaks obtained by diffuse reflectance Fourier transform mid‐infrared spectroscopy (DRIFTS) for characterizing the soil organic matter (SOM) composition of a Haplic Chernozem. Soils were collected from the Static Fertilization Experiment, Bad Lauchstädt, Germany, during 5 years from the farmyard manure (FYM), mineral fertilizer (NPK), combination (FYM + NPK) and no fertilizer (Control) treatments. Soils were extracted with hot water (HWE), and fractionated by size and density. Bulk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
179
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(194 citation statements)
references
References 38 publications
13
179
0
2
Order By: Relevance
“…Considering that the long-term fertilization did not affect the amounts of SOC detected in the clay fraction, it is not as straightforward for phenol to explain the effect of clay on its sorption. Recently, however, advanced spectroscopic methods revealed qualitative differences in the composition of soil organic matter at the clay fractions from these soil variants (Demyan et al, 2012). It was suggested that soil organic matter of clay consists of at least two different fractions: one responsive to environmental change, like induced by long-term fertilization, and the other not (Leifeld and Kö gel-Knabner, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the long-term fertilization did not affect the amounts of SOC detected in the clay fraction, it is not as straightforward for phenol to explain the effect of clay on its sorption. Recently, however, advanced spectroscopic methods revealed qualitative differences in the composition of soil organic matter at the clay fractions from these soil variants (Demyan et al, 2012). It was suggested that soil organic matter of clay consists of at least two different fractions: one responsive to environmental change, like induced by long-term fertilization, and the other not (Leifeld and Kö gel-Knabner, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…KBr-pellet), DRIFT or ATR, depends on parameters such as the sample size, the information needed (bulk versus surface analysis) or the time required for the sample preparation. Currently, the improved design of DRIFT accessories has made this technique widely used for studying soil compounds (Aguiar, et al, 2013;Calderon, et al, 2011aCalderon, et al, , 2011bDemyan, et al, 2012;Ellerbrock, et al, 2009;Francioso, et al, 2009;Leue, et al, 2010;Ludwig, et al, 2008;Minasny, et al, 2008); ATR is also now being widely used (Artz, et al, 2008;Gezic, et al, 2012;Neves-Fernandes, et al, 2010;Vergnoux, et al, 2011).…”
Section: Attenuated Total Reflectance (Atr)mentioning
confidence: 99%
“…This technique was introduced by Nguyen, et al (1991) for studying soil chemical composition and was subsequently used to investigate SOM and the chemical composition of humic substances, as well as the effect of amendment practice on soil (Aguiar, et al, 2013;Calderon, et al, 2011aCalderon, et al, , 2011bDemyan, et al, 2012;Ellerbrock, et al, 2009;Ferrari, et al, 2011;Janik, et al, 2007a;Kaiser, et al, 2007;Leue, et al, 2010;Ludwig, et al, 2008;Minasny, et al, 2008;Reeves III and Smith, 2009). It has also been applied to study many other agricultural related aspects such as the composition of different coal ranks (Chen, et al, 2012;Li, et al, 2010) and their soluble SOM fraction (Gezic, et al, 2012;Ghosh, et al, 2009), the chemistry of waste and compost materials (Huber-Humer, et al, 2011;Salati, et al, 2013;Smidt and Meissl, 2007), the decomposition processes of forest litter (Duboc, et al, 2012;Nault, et al, 2009;Osono, et al, 2011;Tatzber, et al, 2010), the chemical structure of pyrogenic organic matter (OM) Nocentini, et al, 2010) and the behaviour of chemical compounds adsorbed on clays (Aochi and Farmer, 2011;Dorado, et al, 2010).…”
Section: Diffuse Reflectance Infrared Fourier Transform (Drift)mentioning
confidence: 99%
See 1 more Smart Citation
“…The SOM composition can be determined in terms of organic matter functional groups using Fourier transform infrared (FTIR) spectroscopy (e.g., Demyan et al, 2012) or nuclear magnetic resonance (NMR) spectroscopy (e.g., Celi et al, 1997;Schaumann et al, 2013). The potential wettability of SOM was characterized by the ratio between the FTIR signal intensities of hydrophobic aliphatic C-H groups and hydrophilic C = O groups (Ellerbrock et al, 2005).…”
Section: Introductionmentioning
confidence: 99%